Risk of burnout syndrome and explore the factors influencing burnout among nurses in selected hospitals at Himachal Pradesh - Kumari, Kajal; Mayan, Uma (International Journal of Research in Medical Sciences, 2022)
Background: Nurses burnout is a common occurrence marked by a decrease in a nurse's energy, which displays as emotional tiredness, a lack of desire, and emotions of dissatisfaction, as well as a decrease in work efficacy. The aim of study was to assess the risk of burnout syndrome and explore the factors influencing burnout among nurses who are working in emergency ward and critical care units. Methods: The descriptive design was adopted and the sample was selected by non-probability convenient sampling technique. The sample comprises of 200 nurses from emergency and critical care units were selected. The data was gathered by using a 5-point Likert scale and a checklist. Results: The majority of the participants 95 (47.5%) were had high risk of burnout related to physical and psychological exhaustion whereas in self detachment majority of the participants 111 (55.5%) were had high risk of burnout and most of the study participants 101 (50.5%) were had high risk of burnout in self-realization. The risk of burnout syndrome was significant with designation, shift of duty, work overload and attended any workshop, continuing nursing education (CNE), and conference related to burnout syndrome (p<0.05). Conclusions: There was high risk of burnout identified among critical care units and emergency ward nurses. To lessen the severity of burnout, a preventive and therapeutic plan is required like maintain a safe working environment to prevent incidents, provide adequate resources to prevent stress caused by the shortage of staff, rotate nursing staff to work in other wards for professional development and promote open communication to allow team work.